Investigation of the role of stray cats for transmission of toxoplasmosis to humans and animals living in İzmir, Turkey - Muhammet Karakavuk; Hüseyin Can; Nebahat Selim; Berna Yeşilsiraz; Evren Atlı; Esra Atalay Şahar; Ferda Demir; Aytül Gül; Hüseyin Gökhan Özdemir; Nuray Alan; Mustafa Yalçın; Onur Özkurt; et al. (Journal of Infection in Developing Countries)
Introduction: Toxoplasma gondii is a protozoan parasite that has a widespread distribution among mammalians and birds. One of the reasons for the high prevalence may be due to ingesting oocyst disseminated by stray cats’ feces. In Turkey, most of the citizens are closely associated with stray cats and they love to pet and feed them on the streets. In this study, we aimed to determine the prevalence of T. gondii DNA in feces of stray cats living in İzmir, Turkey in order to identify the transmission potential to humans and other animals.